Cardioprotective effects of intracoronary administration of 4-chlorodiazepam in small and large animal models of ischemia-reperfusion. (1st December 2016) - Tsamatsoulis, Michalis; Kapelios, Chris J.; Katsaros, Lambros; Vakrou, Stella; Sousonis, Vasilis; Sventzouri, Stefania; Michelinakis, Nicholas; Perrea, Despoina N.; Anastasiou-Nana, Maria; Malliaras, Konstantinos
Abstract: Background: The Translocator Protein (TSPO) of the mitochondrial membrane has been recognized as a potential therapeutic target for mitigation of myocardial ischemia-reperfusion injury. Administration of 4-chlorodiazepam (4-CLD), a TSPO ligand, has been shown to confer acute cardioprotective effects in small animals; however, long-term studies and studies in clinically-relevant large animal models are lacking. In the present study we investigated a potential cardioprotective effect of intracoronary administration of 4-CLD in small and large animal models of ischemia-reperfusion. Methods: Acute myocardial infarction was induced in 38 Wistar rats and 29 farm pigs by ligation of the left anterior descending coronary artery, followed by reperfusion. Animals were randomized to undergo intracoronary infusion of 2 μM 4-CLD or vehicle just prior (pigs) or immediately after (rats) reperfusion. Infarcted rats were euthanized either after 1 h of reperfusion (for histological assessment of the "no reflow" area) or after 60 days (for serial evaluation of cardiac function and structure by echocardiography and assessment of infarct size). Infarcted pigs were euthanized after 2 h of reperfusion for histological assessment of infarct size and "no reflow" area. Results: In infarcted rats, intracoronary infusion of 4-CLD resulted in acute reduction of the "no reflow" area and conferred durable long-term structural and functional benefits (reduction in infarct size, attenuation of adverse remodeling, improvement in global systolic function). In infarcted pigs, intracoronary infusion of 4-CLD was well-tolerated from a hemodynamic standpoint and resulted in acute reduction in infarct size, reduction in "no reflow" area and more rapid resolution of ST-segment elevation. Conclusions: In a rat model of myocardial infarction, intracoronary administration of 4-CLD attenuated the "no reflow" phenomenon and produced long-term structural and functional benefits. In a porcine model of myocardial infarction intracoronary administration of 4-CLD did not raise safety concerns and conferred acute cardioprotective effects.